Comparative analysis of the efficacy of oblique lateral interbody fusion versus transforaminal lumbar interbody fusion in the treatment of lumbar disc herniation - Daodong Chen; Tao Liu; Kunyang Du; Zhenjun Zhu (Scientific Reports)
Abstract Lumbar disc herniation (LDH) often necessitates surgical intervention when conservative treatments fail. Oblique Lateral Interbody Fusion (OLIF) and Transforaminal Lumbar Interbody Fusion (TLIF) are two commonly used techniques for treating LDH, each offering distinct surgical approaches. This study aimed to compare the efficacy of OLIF versus TLIF in terms of pain relief, functional outcomes, spinal alignment correction, fusion success, and postoperative recovery. A retrospective study was conducted on 133 patients who underwent either OLIF (n = 68) or TLIF (n = 65) between January 2020 and December 2022. Data on patient demographics, pain and functional outcomes (measured by Visual Analogue Scale [VAS] and Oswestry Disability Index [ODI]), radiological outcomes (sagittal and coronal Cobb angles, apical vertebra deviation), fusion and collapse rates, and postoperative recovery (ambulation time and hospitalization duration) were collected. Statistical analysis was performed using t-tests and chi-square tests, with significance set at P < 0.05. Both groups demonstrated significant postoperative improvements in pain and functional outcomes. OLIF resulted in significantly better long-term pain reduction (VAS 1.99 ± 0.67 vs. 2.29 ± 0.92, P = 0.03) and greater spinal alignment correction, particularly in sagittal Cobb angle and apical vertebra deviation (P < 0.001). The fusion rate was similar between OLIF (97.92%) and TLIF (96.61%, P = 0.56), but OLIF had a lower collapse rate (8.33% vs. 18.64%, P < 0.001). OLIF also facilitated faster postoperative recovery, with earlier ambulation and shorter hospitalization time (P < 0.001 for both). While both OLIF and TLIF are effective for treating LDH, OLIF offers superior long-term pain relief, better spinal alignment correction, reduced collapse rates, and faster recovery. These findings suggest that OLIF may be a more advantageous option for patients requiring lumbar interbody fusion.